2012
DOI: 10.1136/tobaccocontrol-2011-050294
|View full text |Cite
|
Sign up to set email alerts
|

Stages of the cigarette epidemic on entering its second century

Abstract: Objectives A four-stage model of the cigarette epidemic was proposed in 1994 to communicate the long delay between the widespread uptake of cigarette smoking and its full effects on mortality, as had been experienced in economically developed countries where cigarette smoking became entrenched decades earlier in men than in women. In the present work, the question of whether qualitative predictions from the model have matched recent trends in smoking and deaths from smoking in countries at various levels of ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
415
1
31

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(474 citation statements)
references
References 14 publications
27
415
1
31
Order By: Relevance
“…In elderly patients (> 66 years), the proportion of never smoking females was significantly higher, 17% versus 5% among males. The changing trends in smoking habits, indicates that the male and female proportions of deaths due to smoking induced cancers are converging and may probably cross over in some industrial countries [25]. It has been suggested that females are more susceptible to develop lung cancer from smoking than males.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In elderly patients (> 66 years), the proportion of never smoking females was significantly higher, 17% versus 5% among males. The changing trends in smoking habits, indicates that the male and female proportions of deaths due to smoking induced cancers are converging and may probably cross over in some industrial countries [25]. It has been suggested that females are more susceptible to develop lung cancer from smoking than males.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
“…The percentage of daily smokers in Norway as in other developed countries has steadily decreased since 1990, and in 2015, the age-standardized prevalence of daily smoking was 15% in both men and women [24]. However, the rates of occurrence of lung cancer related to smoking lag behind smoking rates by about 20 years [25]. Hence, the expected decrease in lung cancer incidence due to decreased smoking is now probably seen among men, but not yet in women.…”
Section: Environmental Agentsmentioning
confidence: 99%
“…Yet, there are some signs that smoking among low-SEP groups is more resilient to antismoking measures than previously predicted (Thun et al, 2012). Even though smoking has decreased among all socio-economic groups, some studies have found that differences between groups have remained stable or even increased over time (Escobedo and Peddicord, 1996;Giskes et al, 2005;Peretti-Watel et al, 2009), which suggest that that diffusion has been blocked or delayed.…”
Section: Diffusion Of Cigarette Smoking Behaviormentioning
confidence: 94%
“…The pattern was similar in Norway, although peak cigarette consumption was lower and occurred more than 10 years later (around 2100 cigarettes per year in 1975). Given the shape of the cigarette consumption and the cigarette smoking prevalence curves over time, the rise and fall of cigarette smoking has typically been described as an epidemic (Lopez et al, 1994;Thun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Varios estudios han comprobado la asociación entre clase social y variables como salud autopercibida, salud mental y conductas relacionadas con la salud (3,(6)(7). El tabaquismo, por ejemplo, empieza primero en hombres y en personas de clases privilegiadas, para después pasar a las mujeres y personas de clases trabajadoras (11). Sobre la actividad física, otra importante variable de salud pública, hay estudios que muestran que las personas de clases trabajadoras realizan menos ejercicio físico (12,13), mientras que otros notifican una mayor prevalencia de inactividad en las clases sociales más privilegiadas (14).…”
unclassified